WE7.5 Hand trauma Tetanus Immunisation: a tertiary trauma centre experience. (9th August 2022) - Labib, Amir; Nguyen, Nga; Banks, Jamie; Moledina, Jamil
Abstract: Aims: To evaluate adherence of hand trauma service at a tertiary trauma centre to Public Health of England guidance on tetanus immunisation. Methods: Prospective data collection of all adult hand trauma injuries between March and June 2021. The first cycle was conducted within the first two weeks of March followed by the introduction of a tetanus immunisation booster flowchart based on the Public Health England guidance. The second cycle was conducted within the first two weeks of June. Results: Of 435 cases reviewed, 380 patients met the inclusion criteria. 69% of cases were male with a mean age of 40 years. Laceration via a sharp object was the most common mechanism of injury followed by machine-related injury representing 44% and 21% respectively. Soft tissue lacerations were by far the most common injury representing 46% of cases. This is the percentage of unnecessary prescription of tetanus booster doses in patients presented with clean wounds falls from 80% in the first cycle to 17% in the second cycle. This reflected in saving the trust £693 within just the period of the first two weeks of June. Conclusions: The use of an easy-to-follow chart for tetanus immunisation when dealing with hand trauma patients led to a significant reduction of unnecessary prescriptions and costs.